Relationship Marketing Implementation of Commitment and Satisfaction in Inpatients in Class III of Buleleng District Hospital - Qamariyah Qamariyah (Journal for Quality in Public Health, 2020)
Commitment and patient satisfaction in hospital services is a priority of the hospital, especially in the inpatient room. Therefore we need methods to make this happen. The purpose of this study is the Effect of Relationship Marketing Implementation on Satisfaction and Commitment in Inpatients in Class III of Buleleng District Hospital. The research method was observational analytic with cross-sectional design. The population is inpatients in class III with a sample of 174 respondents taken by random sampling techniques according to criteria. Using logistic regression statistical analysis. The results of this study are the influence of Relationship Marketing Implementation on the Satisfaction and Commitment of Inpatients in Class III of Buleleng District Hospital, this is indicated by the p-value <α 0.05 and hospital service factors as well as the characteristics of respondents affect the Satisfaction and Commitment of Inpatients Inpatient in Class III of Buleleng Regency Hospital. In conclusion, the implementation of Relationship Marketing 5 times has the opportunity to increase Satisfaction and Commitment in Inpatients in Class III of Buleleng Regency Hospital, the characteristics of respondents 7 times have the opportunity to increase Satisfaction and Commitment in Inpatients in Class III of RSUD in Buleleng Regency and hospital services 8 times have the opportunity to increase Satisfaction and Commitment to Inpatients in Class III of Buleleng District Hospital. Relationship Marketing implementation concluded that it was good to be implemented in increasing Commitment and Satisfaction in Inpatients in Class III of Buleleng District Hospital